2010
DOI: 10.1128/mcb.01876-08
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Regulatory Element in Human Somatic Wee1 Mediates Cyclin A/Cdk2 Binding and Crm1-Dependent Nuclear Export

Abstract: Sophisticated models for the regulation of mitotic entry are lacking for human cells. Inactivating human cyclin A/Cdk2 complexes through diverse approaches delays mitotic entry and promotes inhibitory phosphorylation of Cdk1 on tyrosine 15, a modification performed by Wee1. We show here that cyclin A/Cdk2 complexes physically associate with Wee1 in U2OS cells. Mutation of four conserved RXL cyclin A/Cdk binding motifs (RXL1 to RXL4) in Wee1 diminished stable binding. RXL1 resides within a large regulatory regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 61 publications
2
50
1
Order By: Relevance
“…S2). This response is reminiscent of feedback by Cdk1 to prevent its own inhibition by phosphorylating Wee1 and Cdc25C, and suggests similar feedback between Cdk2 and Wee1/Cdc25A, because Cdk2 phosphorylates Wee1 and Cdc25A (33,34). Cyclin E abundance normally increases in S phase-arrested cells, and we found that cyclin E accumulated to high levels in HU-treated Cdk2 +/+ and Cdk2 +/− cells (Fig.…”
Section: Cdk2 Inhibitory Phosphorylationmentioning
confidence: 53%
“…S2). This response is reminiscent of feedback by Cdk1 to prevent its own inhibition by phosphorylating Wee1 and Cdc25C, and suggests similar feedback between Cdk2 and Wee1/Cdc25A, because Cdk2 phosphorylates Wee1 and Cdc25A (33,34). Cyclin E abundance normally increases in S phase-arrested cells, and we found that cyclin E accumulated to high levels in HU-treated Cdk2 +/+ and Cdk2 +/− cells (Fig.…”
Section: Cdk2 Inhibitory Phosphorylationmentioning
confidence: 53%
“…2, A and B). Importantly, kinases implicated previously in Wee1 turnover, such as Cdk1-cyclin B1, CK2, PLK1, or Cdk2-cyclin A2, were not inhibited by SR-653234 (7,8,12,18). Dose response measurements of kinases that were inhibited by SR-653234 by 65% or more in single-dose measurements provided evidence that the IC 50 s for inhibiting LKB1, FLT3, CK1␦, and CK1⑀ were 92, 100, 161, and 540 nM, respectively (Fig.…”
Section: Sr-653234 Selectively Stabilizesmentioning
confidence: 94%
“…Alternatively, the S472A and L483F mutations may disrupt binding to another protein required for Wee1 turnover. Indeed, a recent paper demonstrates that cyclin A1/Cdk2 binds somatic Wee1 kinase at multiple sites including Leu 483 and Arg 611 (25). These two sites were identified via our mutagenesis approach as required for Wee1 turnover ( Fig.…”
Section: Discussionmentioning
confidence: 99%